Spatial analysis and cost-benefit assessment of climate change adaptation in rice-based agrifood systems of select Asian Mega Deltas - Nelson, Katherine; Vu, Trang; Raviz, Jeny; Villano, Lorena; Laborte, Alice; Bich, Ngoc Vu Thi; Giles, James; Balanza, Jane Girly; Youngberg, Brayden; Rosenstock, Todd S.; Bhandari, Humnath; Nguyen, Tran Bao (International Rice Research Institute, 2025)
The Asian Mega Deltas (AMDs) are critical regions for global food security, nutrition, and poverty alleviation, yet they face significant climate change vulnerabilities. This report assesses the climate-related risks affecting rice-based agrifood systems in the Mekong and Ganges Brahmaputra deltas, including flooding, heat stress, saline intrusion, and changing precipitation patterns. To address these challenges, the report outlines a comprehensive analytical framework for adaptation planning that encompasses policy reviews, climate-risk mapping, crop suitability analysis, vulnerability assessment, cost-benefit evaluation, and market analysis. Findings reveal that integrating climate-resilient practices, such as rice-watermelon and rice-fish systems, can enhance income and sustainability. The results also emphasize the need for robust and targeted investment in infrastructure and capacity building, as well as coordinated efforts among stakeholders, to develop effective adaptation strategies. By prioritizing resilience in agricultural practices, the AMDs can improve livelihoods and ensure long-term food security for their populations amid escalating climate risks. (The report will be available soon)